Social transformations and distribution of pirated media content on the example of video games - Євген Малюк (Cхід)
The article examines the history of the distribution of pirated content and methods of combating it using the example of video games. The ambivalent impact of the phenomenon of piracy on sociocultural processes in societies, especially those that radically changed their social structure at the end of the 20th – beginning of the 21st century, is demonstrated. The author proceeds from the fact that piracy arose on the basis of the absence of the so-called “copyright culture” transformed societies, allowed individual economic actors to get rich illegally and quickly, but at the same time acted as a massive display of technical intelligence, a creative impulse to create one’s own video content in these societies and the formation of relevant regional markets, and also contributed to the development of many technical talents currently working on digitalization of socio-economic processes around the world.